Pavlov and Associationism - Mackintosh, Nicholas J. (The Spanish Journal of Psychology, 2003)
Pavlov’s contribution to experimental psychology was to invent a technique that allowed him to undertake a prolonged and systematic series of well-controlled experiments that, astonishingly enough, uncovered many if not most of the phenomena of what is rightly called Pavlovian conditioning. It was not for another 30 years or more that Englishspeaking psychologists began to match that achievement. Of course there have been new developments and discoveries since his time. Two examples are discussed: the important role of variable associability or attention even in simple conditioning, and the rigorous application of associative learning theory to the behavior of adult humans.